Durable past - sustainable future (TU Delft OPEN Publishing, 2025)
The section Heritage & Architecture of the Faculty of Architecture at Delft University of Technology deals with the built environment in terms of conservation, refurbishment and re-use. Reflecting the department philosophy, this book focuses on the durability and sustainability of existing buildings (heritage in a broad sense, from historic buildings to listed monuments), considered in terms of material and building techniques, form and function, and part of the wider context of sites and cities. At the basis stands the Heritage triangle: Design - Cultural value - Technology. This book is part of a series of books produced in cooperation with and financed by the Stichting Rondeltappe-Bernoster-Kemmers. All books of the series have been reviewed and edited by Silvia Naldini, Section of Heritage & Architecture, Faculty of Architecture and the Built Environment, Delft University of Technology, The Netherlands.